Implementasi Kebijakan Pengembangan Koleksi Di Perpustakaan STIKES Muhammadiyah Gombong - Desy Setiyawati (UPT Perpustakaan UIN Prof. K.H. Saifuddin Zuhri Purwokerto, 2021)
This study aims to determine the extent of the implementation of the collection development policies in the STIKES Muhammadiyah Gombong Library and the obstacle it faces. The existence of a collection in library is a crucial factor and can be used to determine the level of library utilization whether the library is being used properly or not by users. In order for the collection to be efficient and can be used optimally, library need to plan to develop collections, namely by formulating collection development policies and implementing them in library management. The research method used in this research is descriptive qualitative data collection techniques through interviews and literatur study. The results showed that the collection development policy that had been carried out in the STIKES Muhammadiyah Gombong Library was by selecting, acquiring, evaluating, and weeding the collections. This type of collection consists of print and non-print. Meanwhile, collections are procured through purchases, subscriptions, and gifts/donations/grants. The obstacles faced are that suggestions from users have not been able to meet the needs of planned collection, there is no clear standard regarding the comparison of the number of collections in terms of form and language, there are no rules if in the future there is an urgent need in collection development.